Evaluation of cognitive impairment by the Montreal Cognitive Assessment in patients with aneurysmal subarachnoid haemorrhage: prevalence, risk factors and correlations with 3 month outcomes. Issue 11 (31st July 2012) - Wong, George Kwok Chu; Lam, Sandy; Ngai, Karine; Wong, Adrian; Mok, Vincent; Poon, W S; ,
Abstract : Objective: Identification of patients with aneurysmal subarachnoid haemorrhage (aSAH) with cognitive impairment is important for patient management (medical treatment, cognitive rehabilitation and social arrangements). The Montreal Cognitive Assessment (MoCA) is currently recommended over the Mini-Mental State Examination (MMSE) by the US National Institute of Neurological Disorder, in the chronic post-stroke setting. We hypothesised that the MoCA has a better correlation with functional outcome at 3 months than the MMSE. Methods: We carried out a prospective observational study in Hong Kong over a 2 year period, recruiting patients aged 21–75 years with aSAH admitted within 96 h of ictus. The assessments included the modified Rankin Scale, Lawton Instrumental Activity of Daily Living (IADL), Short Form-36, MoCA and MMSE at 3 months after ictus. Analyses were carried out to compare MoCA with MMSE. Results: 90 patients completed the 3 month assessments. Cognitive impairment (MoCA <26) was determined in 73% of patients at 3 months. Delayed cerebral infarction explained the 31–38% variance in cognitive outcomes (MMSE and MoCA) at 3 months. MoCA demonstrated good discrimination of favourable neurological and IADL outcomes similar to the MMSE in receiver operating characteristics curve analyses. Conclusions: MoCA defined cognitive impairment was common at 3 months after aSAH and MoCA correlated with functional outcomes similar, but not superior, to the MMSE. The study is registered at ClinicalTrials.gov of the US National Institutes of Health (NCT01038193 ).